Reconstruction of laboratory press in order to obrain rubber products by vulcanization - Slavkovic, Lazar; Nedic, Bogdan (Journal of Production Engineering, 2019)
Intensive development in field of polymer materials put on the need for laboratorz equipment for different purposes. With an increase in the number of polymer materials and with application rising, elastomers play an important role in the industry. This work describes the method of reconstruction laboratory press machine. This work describes the method of reconstruction of laboratory press machine in press machine for production of rubber parts by compression molding. Furthermore, this work provides basic information about processing technologies and rubber vulcanization. Reconstruction of laboratory press machine will enable production of samples for testing properties of different kind of rubber compound, for design and testing various tools and its will also enable design and production rubber parts.